Method for manufacturing toner for electrostatic image development

JP7936716B2Active Publication Date: 2026-10-16KAO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022188308
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2026-10-16
Estimated Expiration
2042-11-25

AI Technical Summary

Benefits of technology

【0010】 本発明の方法により、粉砕性及び耐久性に優れた静電荷像現像用トナーを製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936716000001
    Figure 0007936716000001
  • Figure 0007936716000002
    Figure 0007936716000002
  • Figure 0007936716000003
    Figure 0007936716000003
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development that excels in grindability and durability.SOLUTION: There is provided a method for manufacturing a toner for electrostatic charge image development that contains a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C is a polycondensation product of an alcohol component containing 80 mol% or more of ethylene glycol and a carboxylic acid component containing 80 mol% or more of an aliphatic dicarboxylic acid compound, and the amorphous polyester resin A is a polycondensation product of an alcohol component containing 80 mol% or more of C2-6 aliphatic diol and a carboxylic acid component. The manufacturing method includes a step in which a mixture containing the crystalline polyester resin C and the amorphous polyester resin A is melted and kneaded by an open roll-type biaxial kneader provided with two rolls differing in a circumferential speed, where a set temperature on a raw material supply side of a high rotation roll having a higher circumferential speed of the open roll-type biaxial kneader is 150°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for manufacturing electrostatic image developing toner used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing, and the like. [Background technology]

[0002] Crystalline polyester resins are known to be effective in improving the low-temperature fixation properties of toner as binder resins, and their use in combination with amorphous resins is also being considered.

[0003] Patent Document 1 discloses a toner containing at least a crystalline polyester and a release agent, characterized in that the toner contains first silica fine particles with a volume average particle diameter of 50 nm or less inside the toner, and the toner surface contains second silica fine particles produced by a sol-gel method with a volume average particle diameter of 50 nm or more and 200 nm or less.

[0004] Patent Document 2 discloses a method for producing toner for electrostatic image development, comprising the step of melting and kneading a mixture containing a binder resin and wax, wherein the binder resin contains an amorphous resin and a crystalline resin, and the amorphous resin contains an amorphous polyester (A) obtained by condensation polymerization of an alcohol component containing an aliphatic diol (a) having 3 or 4 carbon atoms having a hydroxyl group bonded to a secondary carbon atom and an aliphatic diol (b) consisting of one or more α,ω-linear alkanediols having 2, 4, 6, or 8 carbon atoms, and a carboxylic acid component, and the mass ratio of the amorphous resin to the crystalline resin (amorphous resin / crystalline resin) is 55 / 45 to 95 / 5.

[0005] Patent Document 3 discloses an invention relating to a pulverized toner produced by a melt-kneading method, which contains amorphous polyester A and crystalline polyester C, wherein the amorphous polyester A is a polycondensate of an alcohol component containing an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom having 3 to 5 carbon atoms and a carboxylic acid component containing an aromatic dicarboxylic acid compound, and the crystalline polyester C is a polycondensate of an alcohol component containing an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2019-159022 [Patent Document 2] Japanese Patent Publication No. 2014-85587 [Patent Document 3] Japanese Patent Publication No. 2018-59964 [Overview of the project] [Problems that the invention aims to solve]

[0007] However, when manufacturing toner using crystalline polyester resin and amorphous resin, amorphous polyester resin obtained using aliphatic diols with relatively short carbon chains has higher compatibility with crystalline polyester resin compared to resin obtained using aromatic diols such as alkylene oxide adducts of bisphenol A, but further improvements are needed in the pulverizability and durability of the compound.

[0008] This invention relates to a method for manufacturing a toner for electrostatic image developing that has excellent pulverizability and durability. [Means for solving the problem]

[0009] The present invention relates to a method for producing a toner for electrostatic image development containing a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C is a polycondensate of an alcohol component containing 80 mol% or more of ethylene glycol and a carboxylic acid component containing 80 mol% or more of an aliphatic dicarboxylic acid compound, and the amorphous polyester resin A is a polycondensate of an alcohol component containing 80 mol% or more of an aliphatic diol having 2 to 6 carbon atoms and a carboxylic acid component, and the method includes a step of melt-kneading a mixture containing the crystalline polyester resin C and the amorphous polyester resin A using an open-roll twin-screw kneader equipped with two rolls with different peripheral speeds, wherein the set temperature on the raw material supply side of the high-speed roll with the higher peripheral speed of the open-roll twin-screw kneader is 150°C or lower. [Effects of the Invention]

[0010] The method of the present invention makes it possible to manufacture a toner for electrostatic image development that has excellent pulverizability and durability. [Modes for carrying out the invention]

[0011] The present invention is characterized by the use of a crystalline polyester resin and an amorphous resin, obtained using predetermined raw material monomers, when manufacturing an electrostatic image developing toner containing a crystalline polyester resin and an amorphous resin, and by using an open-roll twin-screw kneader with high-speed rolls adjusted to a predetermined temperature in the melt-kneading process. The reason why an electrostatic image developing toner with excellent pulverability and durability can be obtained by the method of the present invention is not clear, but it is presumed to be as follows.

[0012] When an amorphous polyester resin (amorphous polyester resin A) obtained using an aliphatic diol with 2 to 6 carbon atoms as the main alcohol component is melt-kneaded in a twin-screw extruder, the low molecular weight components of amorphous polyester resin A tend to volatilize, resulting in a decrease in the pulverizability of the kneaded material. This is thought to be because the twin-screw extruder is a closed-type kneader, making temperature control during kneading difficult, causing the temperature to become very high, and the low molecular weight components volatilize during cooling immediately after kneading. In contrast, by using an open-roll twin-screw kneader with high-speed rolls adjusted to a predetermined temperature, it is possible to adjust the high-speed rolls to a predetermined temperature and simultaneously perform cooling with low-speed rolls, even though it is an open-type kneader. This suppresses excessive temperature rise during kneading and cooling immediately after kneading. Furthermore, by using a crystalline polyester resin (crystalline polyester resin C) obtained using ethylene glycol as the main component of the alcohol component, the number of carbon atoms in the alcohol component of crystalline polyester resin C and the alcohol component of amorphous polyester resin A are similar, i.e., the distance between ester groups is similar. As a result, the interaction between the two is strong, capturing the low molecular weight components in amorphous polyester resin A and improving the dispersibility of crystalline polyester resin C in amorphous polyester resin A. Consequently, it is presumed that the pulverizability of the kneaded material is improved by suppressing the volatilization of low molecular weight components, and the exposure of low molecular weight components and crystalline polyester resin C to the toner particle surface is suppressed, resulting in a toner with excellent durability.

[0013] In the present invention, the crystalline polyester resin C is a polycondensate of an alcohol component containing ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound.

[0014] The crystallinity of a resin is expressed by a crystallinity index defined by the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, i.e., the value of [softening point / maximum endothermic peak temperature]. A crystalline resin is a resin with a crystallinity index of 0.6 or higher, preferably 0.7 or higher, more preferably 0.9 or higher, and 1.4 or lower, preferably 1.2 or lower, more preferably 1.1 or lower. On the other hand, amorphous resins are those in which no endothermic peak is observed, or, if observed, those with a crystallinity index greater than 1.4, preferably greater than 1.5, more preferably 1.6 or higher, or less than 0.6, preferably 0.5 or lower. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, production conditions (for example, reaction temperature, reaction time, cooling rate), and the like. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. For crystalline resins, the maximum endothermic peak temperature is defined as the melting point.

[0015] The content of ethylene glycol in the alcohol component is 80 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more, and 100 mol% or less. When the alcohol component contains a monoalcohol, the content is preferably 98 mol% or less, more preferably 95 mol% or less.

[0016] Examples of other alcohol components include aliphatic diols other than ethylene glycol, such as 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol; alkylene oxide adducts of bisphenol A; aromatic diols such as bisphenol A; and trivalent or higher alcohols such as hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, and trimethylolpropane.

[0017] Examples of the aliphatic dicarboxylic acid-based compound include succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), sebacic acid (carbon number: 10), dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), succinic acid having an alkyl group or alkenyl group in its side chain, anhydrides of these acids, and alkyl esters of these acids wherein the alkyl group has 1 to 3 carbon atoms. Here, the carbon number of the alkyl group when the aliphatic dicarboxylic acid-based compound is an alkyl ester is not included in the above-mentioned carbon number count.

[0018] The number of carbon atoms in the aliphatic dicarboxylic acid compound is, from the viewpoint of hydrophobicity, preferably 4 or more, more preferably 8 or more, still more preferably 10 or more, even more preferably 12 or more, and from the viewpoint of low-temperature fixability, preferably 16 or less, more preferably 14 or less.

[0019] The aliphatic dicarboxylic acid compound may be a saturated aliphatic dicarboxylic acid compound or an unsaturated aliphatic dicarboxylic acid compound, but from the viewpoint of durability, it is preferably a saturated aliphatic dicarboxylic acid compound.

[0020] The content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is 80 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more, and 100 mol% or less from the viewpoint of durability. When the carboxylic acid component contains a monocarboxylic acid compound, the content is preferably 98 mol% or less, more preferably 95 mol% or less.

[0021] Examples of other carboxylic acid components include aromatic dicarboxylic acid compounds such as phthalic acid, isophthalic acid and terephthalic acid, and trivalent or higher carboxylic acid compounds such as trimellitic acid and pyromellitic acid.

[0022] Further, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin C preferably contains a monofunctional monomer.

[0023] Examples of the monofunctional monomer contained in the alcohol component include aliphatic monoalcohols such as caprin alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol and behenyl alcohol.

[0024] Examples of the monofunctional monomer contained in the carboxylic acid component include aliphatic monocarboxylic acids such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.

[0025] From the viewpoint of improving hydrophobicity, monofunctional monomers preferably contain aliphatic monocarboxylic acid compounds and / or aliphatic monoalcohols.

[0026] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monoalcohol is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more, and from the viewpoint of low-temperature fixability, it is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less.

[0027] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more. From the viewpoint of low-temperature fixability, it is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less. Here, the carbon number of the alkyl group when the aliphatic monocarboxylic acid compound is an alkyl ester is not included in the above carbon number.

[0028] The content of monofunctional monomers is preferably 1 mol% or more, more preferably 3 mol% or more, and even more preferably 5 mol% or more, in the raw material monomer (in the total amount of alcohol and carboxylic acid components), and from the viewpoint of low-temperature fixability, it is preferably 30 mol% or less, more preferably 20 mol% or less, and even more preferably 15 mol% or less.

[0029] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol and carboxylic acid components.

[0030] The equivalent ratio of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or higher, more preferably 0.9 or higher, from the viewpoint of durability, and preferably 1.2 or lower, more preferably 1.1 or lower, from the viewpoint of low-temperature fixability.

[0031] Crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and optionally in the presence of an esterification co-catalyst, polymerization inhibitor, etc., preferably at a temperature of 120°C to 230°C.

[0032] Examples of esterification catalysts include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine. The amount of esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, and more preferably 1 part by mass or less, per 100 parts by mass of the total amount of alcohol and carboxylic acid components. Examples of esterification co-catalysts include gallic acid. The amount of esterification co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less, per 100 parts by mass of the total amount of alcohol and carboxylic acid components. Examples of polymerization inhibitors include tert-butylcatechol. The amount of polymerization inhibitor used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of alcohol and carboxylic acid components.

[0033] In this invention, the polyester resin may be a polyester resin that has been modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins that have been grafted or blocked with phenol, urethane, epoxy, etc., by methods described in Japanese Patent Publication No. 11-133668, Japanese Patent Publication No. 10-239903, Japanese Patent Publication No. 8-20636, etc. Among modified polyester resins, urethane-modified polyester resins obtained by urethane elongation of polyester resin with a polyisocyanate compound are preferred.

[0034] The softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher, from the viewpoint of low-temperature fixability, and preferably 120°C or lower, more preferably 110°C or lower.

[0035] The melting point of the crystalline polyester resin C is preferably 60°C or higher, more preferably 70°C or higher, from the viewpoint of durability, and preferably 130°C or lower, more preferably 120°C or lower, from the viewpoint of low-temperature fixability.

[0036] The acid value of the crystalline polyester resin C is preferably 1 mg KOH / g or more, more preferably 3 mg KOH / g or more, from the viewpoint of low-temperature fixability, and preferably 20 mg KOH / g or less, more preferably 15 mg KOH / g or less, from the viewpoint of durability.

[0037] The content of crystalline polyester resin C is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more, in the total amount of crystalline polyester resin C and amorphous polyester resin A, from the viewpoint of low-temperature fixability, and preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, from the viewpoint of durability.

[0038] Amorphous polyester resin A is a polycondensate of an alcohol component containing an aliphatic diol with 2 to 6 carbon atoms and a carboxylic acid component.

[0039] Examples of aliphatic diols with 2 to 6 carbon atoms include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, and 1,6-hexanediol.

[0040] The content of aliphatic diols with 2 to 6 carbon atoms is, from the viewpoint of durability and pulverability, 80 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more, and 100 mol% or less in the alcohol component. If the alcohol component contains trivalent or higher alcohols, it is preferably 95 mol% or less, more preferably 90 mol% or less. When two or more resins are used in combination as amorphous polyester resins, the aliphatic diol content is calculated as a weighted average value obtained by adjusting the content of the aliphatic diols used in each resin in the alcohol component according to the mass ratio of the resins.

[0041] Other alcohol components include aliphatic diols with 7 or more carbon atoms, alkylene oxide adducts of bisphenol A, aromatic diols such as bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trivalent or higher alcohols such as trimethylolpropane, etc.

[0042] From the viewpoint of durability and pulverability, the carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.

[0043] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids with 1 to 3 carbon atoms.

[0044] The content of aromatic dicarboxylic acid compounds is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, of the carboxylic acid component. If the carboxylic acid component contains trivalent or higher carboxylic acid compounds, the content is preferably 98 mol% or less, more preferably 95 mol% or less.

[0045] Other carboxylic acid components include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with hydrocarbon groups, aliphatic dicarboxylic acids such as glutaric acid, adipic acid, and sebacic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids with 1 to 3 carbon atoms.

[0046] Polyethylene terephthalate (PET) may also be used along with the alcohol and carboxylic acid components. Ethylene glycol and terephthalic acid produced by the depolymerization of PET, or a portion thereof, are used as raw material monomers in a polycondensation reaction and incorporated into the polyester resin. PET is an equimolar polycondensate of ethylene glycol and terephthalic acid, and the ethylene glycol and terephthalic acid constituting PET are considered as the alcohol and carboxylic acid components, respectively.

[0047] The PET can be either new virgin PET or recycled PET. Recycled PET refers to material obtained by collecting used PET, washing it as needed, separating it from other materials, crushing it, depolymerizing the crushed material to monomer units, and then resynthesizing it using these monomers as raw materials.

[0048] The IV value of PET is preferably 0.40 or higher, more preferably 0.45 or higher, even more preferably 0.50 or higher, and still more preferably 0.55 or higher. Furthermore, from the viewpoint of low-temperature fixability and homogenization of depolymerization, it is preferably 0.85 or lower, more preferably 0.80 or lower, even more preferably 0.75 or lower, and still more preferably 0.70 or lower. The IV value is the intrinsic viscosity and serves as an indicator of molecular weight.

[0049] Furthermore, the alcohol component may contain a monohydric alcohol, and the carboxylic acid component may contain a monohydric carboxylic acid compound, as appropriate.

[0050] The equivalent ratio (COOH group / OH group) of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component is preferably 0.6 or higher, more preferably 0.7 or higher, even more preferably 0.75 or higher, and preferably 1.2 or lower, more preferably 1.15 or lower, from the viewpoint of adjusting the softening point of the polyester resin.

[0051] The polycondensation reaction conditions between the alcohol component and the carboxylic acid component of the amorphous polyester resin are the same as those for the crystalline polyester resin, except that the preferred reaction temperature is preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, and more preferably 240°C or lower.

[0052] The softening point of amorphous polyester resin A is preferably 90°C or higher, more preferably 100°C or higher, from the viewpoint of durability, and preferably 150°C or lower, more preferably 140°C or lower, from the viewpoint of low-temperature fixability and pulverability.

[0053] Furthermore, the amorphous polyester resin A may be composed of resins with different softening points, from the viewpoint of low-temperature fixability and fixation width. The difference in softening points between the two resins is preferably 10°C or more, more preferably 12°C or more, and preferably 60°C or less, more preferably 30°C or less, and even more preferably 20°C or less.

[0054] The softening point of the amorphous resin (resin AH) with a higher softening point is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher, from the viewpoint of fixing width, and preferably 180°C or lower, more preferably 160°C or lower, and even more preferably 140°C or lower, from the viewpoint of low-temperature fixing properties.

[0055] Furthermore, the softening point of the amorphous resin (resin AL) with a lower softening point is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, from the viewpoint of durability, and preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower, from the viewpoint of low-temperature fixing properties.

[0056] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and preferably 90 / 10 or less, more preferably 80 / 20 or less, and even more preferably 70 / 30 or less.

[0057] The glass transition temperature of amorphous polyester resin A is preferably 40°C or higher, more preferably 50°C or higher, from the viewpoint of durability, and preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 68°C or lower, from the viewpoint of low-temperature fixation.

[0058] The acid value of amorphous polyester resin A is preferably 1 mg KOH / g or more, more preferably 3 mg KOH / g or more, from the viewpoint of low-temperature fixability, and preferably 20 mg KOH / g or less, more preferably 18 mg KOH / g or less, from the viewpoint of durability.

[0059] The number-average molecular weight of amorphous polyester resin A is preferably 1,000 or more, more preferably 1,500 or more, and even more preferably 2,000 or more, from the viewpoint of durability, and preferably 6,000 or less, more preferably 5,000 or less, and even more preferably 4,000 or less, from the viewpoint of low-temperature fixability and pulverability.

[0060] The weight-average molecular weight of amorphous polyester resin A is preferably 4,000 or more, more preferably 6,000 or more, and even more preferably 8,000 or more, from the viewpoint of durability, and preferably 500,000 or less, more preferably 200,000 or less, and even more preferably 150,000 or less, from the viewpoint of low-temperature fixability and pulverability.

[0061] The content of amorphous polyester resin A is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more, of the total amount of crystalline polyester resin C and amorphous polyester resin A, from the viewpoint of durability, and preferably 97% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less, from the viewpoint of pulverability.

[0062] The mass ratio of crystalline polyester resin C to amorphous polyester resin A (crystalline polyester resin C / amorphous polyester resin A) is preferably 3 / 97 or higher, more preferably 5 / 95 or higher, and even more preferably 8 / 92 or higher, from the viewpoint of low-temperature fixability and pulverability, and preferably 30 / 70 or lower, more preferably 25 / 75 or lower, and even more preferably 20 / 80 or lower, from the viewpoint of durability.

[0063] In toner, crystalline polyester resin C and amorphous polyester resin A are included as binder resins.

[0064] Other binder resins include vinyl resins such as styrene-acrylic resin, epoxy resins, polycarbonate, polyurethane, and composite resins containing two or more of these resins.

[0065] The total content of crystalline polyester resin C and amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.

[0066] Furthermore, the binder resin content in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and preferably less than 100% by mass, more preferably 98% by mass or less, and even more preferably 95% by mass or less.

[0067] In addition to the binder resin, the toner may contain additives such as colorants, release agents, charge control agents, magnetic powders, flow improvers, conductivity modifiers, reinforcing fillers such as fibrous materials, antioxidants, and cleaning properties improvers.

[0068] As colorants, dyes, pigments, magnetic materials, etc., used as colorants for toners can be used. Examples include carbon black, phthalocyanine blue, permanent brown FG, brilliant first scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazoel, etc. In this invention, the toner may be either black toner or color toner.

[0069] From the viewpoint of improving the image density of the toner and its low-temperature fixability, the amount of colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of the binder resin.

[0070] Examples of mold release agents include hydrocarbon waxes and their oxides, such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; ester waxes such as carnauba wax, montane wax and their deoxidizing waxes, and fatty acid ester waxes; and fatty acid amides, fatty acids, higher alcohols, fatty acid metal salts, etc., which can be used individually or in combination of two or more.

[0071] The melting point of the release agent is preferably 60°C or higher, more preferably 70°C or higher, from the viewpoint of durability, and preferably 160°C or lower, more preferably 140°C or lower, even more preferably 120°C or lower, and even more preferably 110°C or lower, from the viewpoint of low-temperature fixation.

[0072] The release agent content is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less, per 100 parts by mass of binder resin, from the viewpoint of low-temperature fixability and pulverability of the toner and dispersibility in the binder resin.

[0073] The charge control agent is not particularly limited and may contain either a positively charged charge control agent or a negatively charged charge control agent.

[0074] Positively charged charge control agents include nigrosine dyes, such as "Nigrosine Base EX," "Oil Black BS," "Oil Black SO," "Bontron N-01," "Bontron N-04," "Bontron N-07," "Bontron N-09," and "Bontron N-11" (all manufactured by Orient Chemical Industries, Ltd.); triphenylmethane-based dyes containing tertiary amines as side chains; quaternary ammonium salt compounds, such as "Bontron P-51" (manufactured by Orient Chemical Industries, Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX." Examples include VP435 (manufactured by Clariant), polyamine resins such as AFP-B (manufactured by Orient Chemical Industries, Ltd.), imidazole derivatives such as PLZ-2001 and PLZ-8001 (both manufactured by Shikoku Chemicals, Ltd.), and styrene-acrylic resins such as FCA-701PT and FCA-201-PS (manufactured by Fujikura Chemicals, Ltd.).

[0075] Furthermore, as negative charge control agents, metal-containing azo dyes, such as "Barifast Black 3804," "Bontron S-31," "Bontron S-32," "Bontron S-34," and "Bontron S-36" (all manufactured by Orient Chemical Industries, Ltd.), "Eisenspiron Black TRH," and "T-77" (manufactured by Hodogaya Chemical Co., Ltd.); metal compounds of benzyl acid compounds, such as "LR-147" and "LR-297" (both manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds, such as "Bontron E-81," "Bontron E-84," "Bontron E-88," and "Bontron E-304" (all manufactured by Orient Chemical Industries, Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts, such as "COPY CHARGE NX" Examples include VP434 (manufactured by Clariant), nitroimidazole derivatives, organometallic compounds, etc.

[0076] From the viewpoint of the charge stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the binder resin.

[0077] In this invention, a mixture containing a crystalline polyester resin C and an amorphous polyester resin A, and optionally additives such as a colorant, mold release agent, and charge control agent, is subjected to a melt-kneading process using an open-roll twin-screw kneader.

[0078] The mixture to be mixed can be mixed all at once or in portions, but it is preferable to mix it beforehand in a mixer such as a Henschel mixer or ball mill before supplying it to an open-roll twin-screw mixer.

[0079] An open-roll twin-screw mixer is a type of mixer equipped with two rolls, in which the melting and mixing section is not sealed but open, allowing for easy dissipation of the heat generated during melting and mixing. The open-roll twin-screw mixer used in this invention is equipped with a raw material supply port and a mixed material discharge port located along the axial direction of the rolls, and from the viewpoint of production efficiency, a continuous open-roll twin-screw mixer is preferable.

[0080] The open-roll twin-screw kneader used in the present invention is a kneader equipped with two rolls with different peripheral speeds, namely a high-speed roll with a high peripheral speed and a low-speed roll with a low peripheral speed. In the present invention, from the viewpoint of improving the dispersibility of crystalline polyester resin, it is preferable that the high-speed roll functions as a heating roll and the low-speed roll functions as a cooling roll, that is, it is preferable that the set temperature of the high-speed roll is higher than the set temperature of the low-speed roll. If the set temperatures of the rolls differ on the raw material input side and the kneaded product discharge side, it is preferable that the set temperature of the high-speed roll is higher than the set temperature of the low-speed roll at least on the raw material input side, and it is more preferable that the set temperature of the high-speed roll is higher than the set temperature of the low-speed roll on both the raw material input side and the kneaded product discharge side.

[0081] The temperature of the roll can be adjusted, for example, by the temperature of the heat transfer medium passed through the roll. Each roll may also have its interior divided into two or more sections through which heat transfer mediums with different temperatures are passed.

[0082] The temperature on the raw material input side of the high-speed roll is 150°C or lower, preferably 145°C or lower, more preferably 140°C or lower, from the viewpoint of suppressing the volatilization of low molecular weight components, and preferably 80°C or higher, more preferably 85°C or higher, and even more preferably 90°C or higher, from the viewpoint of melting the crystalline polyester resin.

[0083] On the other hand, the temperature on the mixed material discharge side of the high-speed roll is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 70°C or higher, and preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower, from the viewpoint of improving the dispersibility of the crystalline polyester resin.

[0084] The temperature on the raw material input side of the low-speed roll is preferably 25°C or higher, more preferably 40°C or higher, and preferably 80°C or lower, more preferably 70°C or lower, from the viewpoint of reducing mechanical force during melting and kneading and suppressing heat generation.

[0085] From the viewpoint of improving the dispersibility of the crystalline polyester resin, the temperature on the mixed material discharge side of the low-speed roll is preferably 25°C or higher, more preferably 30°C or higher, and preferably 80°C or lower, more preferably 50°C or lower.

[0086] For both high-speed and low-speed rolls, it is preferable that the temperature on the raw material input side is higher than the temperature on the mixed material discharge side. For high-speed rolls, the temperature difference between the raw material input side and the mixed material discharge side is preferably 5°C or higher, more preferably 20°C or higher, even more preferably 25°C or higher, and preferably 60°C or lower, more preferably 50°C or lower, and even more preferably 35°C or lower, from the viewpoint of preventing the mixed material from detaching from the roll and reducing mechanical force during melt kneading to suppress heat generation. For low-speed rolls, the temperature difference between the raw material input side and the mixed material discharge side is preferably 5°C or higher, and preferably 50°C or lower, from the viewpoint of improving the dispersibility of the crystalline polyester resin and reducing mechanical force during melt kneading to suppress heat generation.

[0087] The temperature on the raw material input side of the high-speed and low-speed rolls refers to the set temperature at the raw material input end, while the temperature on the kneaded material discharge side refers to the set temperature at the kneaded material discharge end.

[0088] The peripheral speed of the high-speed roll is preferably 2 m / min or more, more preferably 10 m / min or more, even more preferably 25 m / min or more, and preferably 100 m / min or less, more preferably 75 m / min or less, and even more preferably 50 m / min or less, from the viewpoint of improving the dispersibility of the crystalline polyester resin and reducing the mechanical force during melt kneading and suppressing heat generation. The peripheral speed of the low-speed roll is preferably 1 m / min or more, more preferably 5 m / min or more, even more preferably 15 m / min or more, and preferably 90 m / min or less, more preferably 60 m / min or less, and even more preferably 30 m / min or less, from the viewpoint of improving the dispersibility of the crystalline polyester resin and reducing the mechanical force during melt kneading and suppressing heat generation.

[0089] Furthermore, there are no particular limitations on the structure, size, or material of each roll. The roll surface has grooves used for mixing, and these grooves can be straight, spiral, wavy, or uneven.

[0090] After melt-kneading, it is preferable to cool the mixture appropriately until it reaches a hardness that allows for pulverization, and to perform pulverization and classification steps as needed to obtain toner particles. Here, cooling refers to cooling the mixture to a temperature between 0°C and 50°C, or to a temperature below the glass transition temperature of the binder resin in the mixture.

[0091] In grinding a compound, the compound may be ground to the desired particle size all at once or in stages. However, from the viewpoint of efficient and more uniform grinding, it is preferable to perform the grinding in two stages: coarse grinding and fine grinding.

[0092] Examples of grinders used for coarse grinding include hammer mills, cutter mills, atomizers, and Rotoplexes.

[0093] For coarse grinding, it is preferable to grind until the maximum diameter is 3 mm or less. For example, a pulverized material with a maximum diameter of 3 mm or less can be obtained by coarsely grinding the kneaded material to a particle size of approximately 0.05 mm to 3 mm, then passing it through a sieve with a mesh size of 3 mm, and obtaining the pulverized material that passes through the sieve.

[0094] Examples of grinders used for fine grinding include fluidized bed jet mills, impact plate jet mills, and other types of jet mills, as well as mechanical mills.

[0095] The degree of fine grinding is preferably adjusted as appropriate according to the desired toner particle size.

[0096] Classifiers used for classification include air-flow classifiers, inertia classifiers, and sieve classifiers. During the classification process, any pulverized material that is removed due to insufficient pulverization may be subjected to the pulverization process again, and the pulverization and classification processes may be repeated as needed.

[0097] In the present invention, it is preferable to further include an external additive step in which the obtained toner particles are mixed with an external additive.

[0098] Examples of external additives include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles. Two or more types may be used in combination. Among these, silica is preferred, and from the viewpoint of toner durability, hydrophobic silica that has been hydrophobicized is more preferred.

[0099] Examples of hydrophobic agents used to hydrophobize the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0100] The average particle size of the external additive is preferably 5 nm or larger, more preferably 10 nm or larger, even more preferably 15 nm or larger, and preferably 250 nm or smaller, more preferably 200 nm or smaller, and even more preferably 90 nm or smaller, from the viewpoint of the toner's chargeability, fluidity, and durability.

[0101] From the viewpoint of the toner's electrostatic properties, fluidity, and durability, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, per 100 parts by mass of toner particles before treatment with the external additive.

[0102] The volume median particle size (D) of the toner obtained by the method of the present invention 50 The volume median particle size (D) is preferably 3 μm or more, more preferably 4 μm or more, and preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated using volume fractions accounts for 50% when calculated from the smallest particle size. Furthermore, if the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is taken as the volume median particle size of the toner.

[0103] The toner obtained by the method of the present invention can be used as is as a one-component developing toner, or as a two-component developing toner mixed with a carrier, in image forming apparatuses using either a one-component developing method or a two-component developing method, respectively. [Examples]

[0104] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way by these examples. The physical properties of resins, etc., can be measured by the following methods.

[0105] [Softening point of resin] Using a flow tester "CFT-500D" (manufactured by Shimadzu Corporation), 1 g of sample is heated at a heating rate of 6°C / min while a load of 1.96 MPa is applied by a plunger, and the sample is extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The amount of plunger descent of the flow tester is plotted against temperature, and the temperature at which half of the sample has flowed out is defined as the softening point.

[0106] [Maximum peak temperature of endothermic resin] Using a differential scanning calorimeter "Q-100" (manufactured by T.A. Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample is weighed into an aluminum pan and cooled from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintained at 0°C for 1 minute. Then, measurements are taken at a rate of 10°C / min. Among the observed endothermic peaks, the temperature of the peak with the largest peak area is defined as the maximum endothermic peak temperature. For crystalline resins, the maximum endothermic peak temperature is defined as the melting point.

[0107] [Glass transition temperature of amorphous resins] Using a differential scanning calorimeter "Q-100" (manufactured by T.A. Instruments Japan), 0.01 to 0.02 g of the sample is weighed into an aluminum pan, heated to 200°C, and then cooled to 0°C at a rate of 10°C / min. Next, the sample is heated at a rate of 10°C / min and the endothermic peak is measured. The temperature at the intersection of the baseline extension below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rise of the peak to the peak apex is defined as the glass transition temperature.

[0108] [Acid value of resins] Measurements will be performed according to the method of JIS K 0070:1992. However, the measurement solvent will be changed from the ethanol and ether mixed solvent specified in JIS K 0070 to a mixed solvent of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and to a mixed solvent of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.

[0109] [Number-average molecular weight and weight-average molecular weight of resins] The number average molecular weight and weight average molecular weight are determined by the gel permeation chromatography (GPC) method according to the following procedure. (1) Preparation of sample solution The resin is dissolved in tetrahydrofuran so that the concentration becomes 0.5 g / 100 mL. Next, this solution is filtered using a fluororesin filter with a pore size of 2 μm (manufactured by Sumitomo Electric Industries, Ltd., trade name: FP-200) to remove insoluble components, to obtain a sample solution. (2) Molecular weight measurement Using the following measurement apparatus and analytical column, tetrahydrofuran is allowed to flow as an eluent at a flow rate of 1 mL per minute, and the column is stabilized in a constant temperature bath at 40°C. 100 μL of the sample solution is injected thereinto to perform the measurement. The molecular weight of the sample is calculated based on a previously prepared calibration curve. For the calibration curve at this time, several types of monodisperse polystyrene of known molecular weight (manufactured by Tosoh Corporation; 2.63×10 3 , 2.06×10 4 , 1.02×10 5 , manufactured by GL Sciences Inc.; 2.10×10 3 , 7.00×10 3 , 5.04×10 4 ) are used as standard samples to prepare the curve. Measurement apparatus: CO-8010 (trade name, manufactured by Tosoh Corporation) Analytical column: GMH XL +G3000H XL (all are trade names, manufactured by Tosoh Corporation)

[0110] [IV value of PET] It can be determined by dissolving in a mixed solvent of phenol / tetrachloroethane (mass ratio) of 60 / 40 at a concentration of 4 g / L, performing measurement with an Ubbelohde viscometer, and calculating according to the following formula. IV=(-1+√(1+4kη)) / (2kC) [In the formula, k=0.33, C=0.004 g / mL, and η=(t1 / t0)-1 (t0: the number of seconds for the solvent alone to fall, t1: the number of seconds for the sample solution to fall).]

[0111] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample is weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. Next, the sample is heated again at a rate of 10°C / min, the heat quantity is measured, and the maximum endothermic peak temperature is defined as the melting point.

[0112] [Average particle size of external additives] The average particle diameter refers to the number-average particle diameter, which is calculated by measuring the particle size (average of the major and minor axes) of 500 particles from scanning electron microscope (SEM) images and using the number-average value of these measurements.

[0113] [Toner volume medium particle size (D 50 )〕 • Measuring instrument: "Coulter Multisizer (Registered Trademark) III" (manufactured by Beckman Coulter, Inc.) • Aperture diameter: 50 μm • Analysis software: "Multisizer (registered trademark) III version 3.51" (manufactured by Beckman Coulter, Inc.) • Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) • Dispersion: Prepared by dissolving polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" [manufactured by Kao Corporation, HLB (Griffin) = 13.6] in the electrolyte to adjust the concentration to 5% by mass. • Dispersion conditions: Add 10 mg of the sample to 5 mL of the dispersion and disperse for 1 minute using an ultrasonic disperser (machine name: US-1 manufactured by SND Corporation, output: 80W). Then, add 25 mL of electrolyte and disperse for another minute using the ultrasonic disperser to prepare the sample dispersion. • Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, the 30,000 particles are measured, and the volume median particle size (D) is determined from the particle size distribution. 50 )

[0114] Resin manufacturing example 1 The alcohol and carboxylic acid components shown in Table 1 were placed in a 5-liter four-necked flask equipped with a thermometer, stainless steel stirring rod, a fall-flow condenser, and a nitrogen inlet tube. The mixture was heated to 200°C over 8 hours in a mantle heater under a nitrogen atmosphere. Subsequently, the esterification catalyst shown in Table 1 was added, and the reaction was carried out at 8.0 kPa until the softening point shown in Table 1 was reached, yielding crystalline polyester resins (resins C1-C6). The physical properties are shown in Table 1.

[0115] [Table 1]

[0116] Resin manufacturing example 2 The alcohol components, carboxylic acid components, esterification catalyst, and esterification co-catalyst shown in Tables 2 and 3 were placed in a 5-liter four-necked flask equipped with a nitrogen inlet tube, a dehydration tube fitted with a fractionation tube through which 98°C hot water was passed, a stirrer, and a thermocouple. Under a nitrogen atmosphere, the flask was kept warm at 180°C for 1 hour, then the temperature was increased from 180°C to 230°C at a rate of 10°C / h, and then polycondensation was carried out at 230°C for 5 hours. The reaction was further carried out at 230°C under reduced pressure of 10 kPa until the softening point shown in Tables 2 and 3 was reached to obtain amorphous polyester resins (resins AH1, AH2, AH6, AL1, AL2, AL5). The physical properties are shown in Tables 2 and 3.

[0117] Resin manufacturing example 3 The alcohol components, carboxylic acid components, PET, esterification catalyst, and esterification co-catalyst shown in Tables 2 and 3 were placed in a 5-liter four-necked flask equipped with a nitrogen inlet tube, stirrer, and thermocouple. Under a nitrogen atmosphere, the flask was kept warm at 180°C for 1 hour, then the temperature was increased from 180°C to 230°C at a rate of 10°C / h, and then polycondensation was carried out at 230°C for 5 hours. The reaction was further carried out at 230°C under reduced pressure of 10 kPa until the softening point shown in Tables 2 and 3 was reached, yielding amorphous polyester resins (resins AH3, AH4, AL3, and AL4). The physical properties are shown in Tables 2 and 3.

[0118] Resin manufacturing example 4 The alcohol components shown in Table 2, carboxylic acid components other than trimellitic anhydride, esterification catalyst, and esterification co-catalyst were placed in a 5-liter four-necked flask equipped with a nitrogen inlet tube, a dehydration tube fitted with a fractionation tube through which 98°C hot water was passed, a stirrer, and a thermocouple. Under a nitrogen atmosphere, the mixture was kept warm at 180°C for 1 hour, then the temperature was increased from 180°C to 230°C at a rate of 10°C / h, and polycondensation was carried out at 230°C for 5 hours. After that, the temperature was lowered to 210°C, trimellitic anhydride as shown in Table 2 was added, and the reaction was carried out at 210°C for 1 hour. The reaction was then further carried out at 210°C under reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, yielding amorphous polyester resin (resin AH5). The physical properties are shown in Table 2.

[0119] [Table 2]

[0120] [Table 3]

[0121] Examples 1-13 and Comparative Examples 2 and 3 (Examples 8 and 9 are for reference only.) 100 parts by mass of the binder resin shown in Table 4, 5 parts by mass of the coloring agent "ECB-301" (manufactured by Dainichi Seika Co., Ltd., phthalocyanine blue (PB15:3)), 3 parts by mass of the release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83℃), 3 parts by mass of the release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd., paraffin wax, melting point: 75℃), and 0.5 parts by mass of the charge control agent "Bontron E-304" (manufactured by Orient Chemical Industry Co., Ltd.) were mixed in a Henschel mixer.

[0122] The obtained raw material mixture was fed via a table feeder to a continuous open-roll twin-shaft mixer "Nidex" (manufactured by Mitsui Mining Co., Ltd.) for mixing to obtain a compound. The continuous open-roll twin-shaft mixer used had a roll outer diameter of 0.14 m and an effective roll length of 0.8 m. The operating conditions were: high-speed roll (front roll) rotation speed of 75 r / min (peripheral speed 33 m / min), low-speed roll (rear roll) rotation speed of 50 r / min (peripheral speed 22 m / min), and roll gap of 0.1 mm. The heating and cooling media temperatures inside the rolls were set as shown in Table 4 for the raw material input side of the high-speed roll and 90°C for the compound discharge side, while the raw material input side of the low-speed roll was set to 65°C and the compound discharge side was set to 30°C. The raw material mixture supply rate was 10 kg / h, and the average residence time was approximately 5 minutes.

[0123] The resulting mixture was cooled to 25°C and coarsely ground using a Rotoplex pulverizer (manufactured by Toa Machinery Co., Ltd.). A sieve with a mesh size of 2 mm was used to obtain coarsely ground material with a particle size of 2 mm or less. The obtained coarsely ground material was finely ground using an I-2 type pulverizer (manufactured by Nippon Pneumatic Co., Ltd.) and classified to obtain medium volume particle size (D 50 This yielded toner particles with a diameter of 6.5 μm.

[0124] Here, the grinding pressure (MPa) when the mixture was finely ground using the I-2 type grinder was measured to evaluate its grindability. The results are shown in Table 4. Lower grinding pressure indicates better grindability.

[0125] Toner was obtained by mixing 100 parts by mass of the obtained toner particles with 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 3000 r / min (peripheral speed 32 m / sec) for 3 minutes.

[0126] Comparative Example 1 Toner was obtained in the same manner as in Example 1, except that a twin-screw extruder "PCM-30" (manufactured by Ikegai Iron Works Co., Ltd.) was used for melt kneading instead of a continuous open-roll twin-screw kneader. The operating conditions for the twin-screw extruder were a barrel setting temperature of 100°C, a shaft rotation speed of 200 r / min (perpendicular speed of shaft rotation of 0.30 m / sec), and a mixture supply rate of 10 kg / h.

[0127] Test example [Toner durability] A toner was installed in a "PagePresto N-4" printing press (manufactured by Casio Computer Co., Ltd., fixing method: contact fixing method, developing method: non-magnetic one-component developing method, developing roll diameter: 2.3 cm), and a diagonal stripe pattern with a blackening rate of 5.5% was continuously printed in an environment of 32°C and 85% humidity. Every 500 sheets, a solid black image was printed to check for the presence of streaks on the image. Printing was stopped when streaks appeared on the image, and continued up to a maximum of 9000 sheets. Durability was evaluated by counting the number of printed pages up to the point where streaks were visually observed on the image, which was defined as the number of pages where streaks occurred due to toner fusion and fixation on the developing roll. The results are shown in Table 4. In the table, ">9000" means that no streaks occurred even after 9000 prints. A higher number of pages without streaks indicates superior toner durability.

[0128] [Table 4]

[0129] Based on the above results, it can be seen that the toners of Examples 1 to 13 exhibit excellent pulverization properties of the kneaded material and good durability, compared to Comparative Example 1, which used a twin-screw extruder for melt kneading; Comparative Example 2, which contained a crystalline polyester resin without ethylene glycol; and Comparative Example 3, which contained an amorphous polyester resin with a small amount of aliphatic diol. [Industrial applicability]

[0130] The electrostatic image developing toner obtained by the method of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing, and the like.

Claims

1. A method for producing a toner for electrostatic image development containing a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C is a polycondensate of an alcohol component containing 80 mol% or more of ethylene glycol and a carboxylic acid component containing 80 mol% or more of an aliphatic dicarboxylic acid compound, and the amorphous polyester resin A is a polycondensate of an alcohol component containing 80 mol% or more of an aliphatic diol having 2 to 6 carbon atoms and a carboxylic acid component, and a mixture containing the crystalline polyester resin C and the amorphous polyester resin A. A method for producing toner for electrostatic image developing, comprising the step of melt-kneading using an open-roll twin-screw kneader equipped with two rolls of different peripheral speeds, wherein the set temperature on the raw material supply side of the high-speed roll with the higher peripheral speed of the open-roll twin-screw kneader is 150°C or lower, the carboxylic acid component of the crystalline polyester resin C contains an aliphatic dicarboxylic acid compound having 8 to 16 carbon atoms, and the carboxylic acid component of the crystalline polyester resin C contains a monofunctional monomer, the monofunctional monomer being an aliphatic monocarboxylic acid compound having 10 to 18 carbon atoms.

2. The manufacturing method according to claim 1, wherein the mass ratio of crystalline polyester resin C to amorphous polyester resin A is 3 / 97 or more and 30 / 70 or less.

3. The method for producing a crystalline polyester resin C, wherein the carboxylic acid component contains a saturated aliphatic dicarboxylic acid compound, according to claim 1.

4. The manufacturing method according to claim 1, wherein the set temperature of the high-speed rolls of the open-roll twin-screw kneader is higher than the set temperature of the low-speed rolls.

Citation Information

Patent Citations

  • Method for manufacturing electrophotographic toner

    JP2007171398A

  • Electrophotographic toner

    JP2009122195A

  • Manufacturing method of toner for electrostatic charge image development

    JP2014085587A

  • toner

    JP2018059964A

  • Binder resin composition for toner

    JP2019066536A